Pengembangan bahan ajar IPS berbasis pendekatan Sains Teknologi Masyarakat (STM) untuk meningkatkan kreativitas siswa - Sitti Jauhar (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Social Sciences as part of education generally has an important role in improving the quality of education, especially in producing qualified students who are able to think critically, creatively, logically, and take the initiative in responding to issues in the community caused by impact the development of science and technology. However, social studies in primary schools nowadays is less associated with social and technological issues that exist in the community, especially those related to technological development and the presence of technology products in the community, as well as its consequences. Social studies in schools is merely following the demands of curriculum that has been written in the textbook. It is not and easy job for teachers to provide conducive conditions for every students. There are active students, quiet students with great academic scores, and there are also students who speak a lot but have low abilities. In fact, there are students with middle to lower academic abilities who feel pressured by social science material that is full of theories, concepts, which are complicated and even difficult to understand. This is what can lead to the lack of meaning in social studies at this time, which will make student activities to be low and passive learning conditions. In fact, the 2013 curriculum (K-13), the teaching approach used in learning process should be positioned as a center of attention (students- centered). Development of social sciences teaching materials using the STM approach forms the teaching process that emphasizes the mastery of science concepts and emphasizes the role of science and technology in various people's lives and fosters a sense of social responsibility towards the impact of science and technology in the community. Through the Community Science approach, 6 domains of science can be developed, namely the concepts, processes, creativity, attitudes, applications, and interrelations aspects.